Determination of OCPs and PCBs in environmental water samples by GC-DLLME optimized by Response Surface Methodology - Dekun Hou; Otgonbayar Khureldavaa; Fujin Zhang; Jiang He; Badgaa Amarsanaa (Mongolian Journal of Chemistry, 2019)
A new sample preparation procedure to determine seven organochlorine pesticides and seven polychlorinated biphenyls in environmental water samples by using a combination of ultrasonic-assisted solvent extraction and dispersive liquid-liquid micro-extraction was established, and the extracted analytes were analyzed by gas chromatography coupled with electron capture detector. Some parameters influencing the extraction efficiency were studied and optimized utilizing response surface methodology. Under the optimum extraction conditions, the method showed wide linear ranges with r2 > 0.9989 and low limits of detection and quantification between 0.16 ~ 2.17 μg/L and 0.53 ~ 7.16 μg/L, respectively. Enrichment factors (EF) were high and ranged from 63 to 116. Relative standard deviations (RSDs) for the extraction of 25 μg/L of each selected OCPs and PCBs were less than 10.2 %. The proposed method was successfully used for targets contaminations determination in different water samples. α-HCH, β-HCH and p,p’-DDE were found in lake water closed to farmland with concentrations of 2.56 μg/L, 4.44 μg/L and 4.74 μg/L, respectively, and other OCPs and PCBs were not found in the corresponding water samples. The relative recoveries of OCPs and PCBs from tap water, river water and lake water at spiking levels of 10 μg/L were in the range of 81.9 ~ 109.7 %, within a relative standard deviation of 1.7 ~ 11.8 %. The results revealed that the proposed method was well suited for the determination of trace amounts of target contaminations in liquid samples.